Geographical generality of bird‐habitat relationships depends on species traits. Issue 11 (8th September 2017) - Bonthoux, Sébastien; Balent, Gérard; Augiron, Steve; Baudry, Jacques; Bretagnolle, Vincent
Abstract: Aim: The environmental filtering process is often considered as static in ecological studies. However, growing evidence shows that species‐environment relationships vary in space and time. In this study, we assessed to what extent bird responses to landscape components can be geographically generalised and whether differences in response generality can be explained by traits. Location: France. Methods: We collected a large bird data set (1968 point counts over two years) with a standardised protocol in three agricultural regions with different levels of intensification in France. We modelled the relationships between the distribution of 26 bird species and three landscape components (percentage of woodland, hedgerow density and landscape heterogeneity) and assessed whether differences between regions in bird responses to landscape components (i.e., landscape‐region interactions) can be explained by three species traits (habitat specialisation, diet and migration strategy). We also examined the response of total species richness. Results: We found that 16 species showed regional differences in their response at least for one of the three landscape variables. Importance of landscape‐region interactions was significantly correlated with two species traits. Responses of specialist species to landscape components were geographically more constant than those of generalists. The geographical variability of responses was higher for migrants than for sedentary species. There were no significant relationships for the diet trait. Species richness responded positively to the three landscape metrics in a similar way in the three regions. Main conclusions: The results underline the need to take into account the spatial differences between species responses to habitats according to their traits when modelling species‐habitat relationships at large scales. From a conservation point of view, we suggest that conservation measures could be generalised at a large scale for specialist species which are declining in agricultural landscapes.